THE IMPLEMENTATION OF ENGLISH TEACHERS’ AUTHENTIC ASSESSMENT IN SMP NEGERI 6 SINGARAJA - Putri, Ni Wayan Astri Monika (Journal of Education Research and Evaluation, 2021)
Authentic assessment is assessment to define students’ reflection of their learning, achievement, motivation, and attitudes during the learning instruction. Implementing authentic assessment reflects real-world situation and allow students to solve problem with possible solutions. This research aimed at investigating the English teachers’ authentic assessment implementation during online learning. This research was descriptive qualitative research. The research subject was three English Teachers in SMP Negeri 6 Singaraja. Then, the research object was the English teachers’ implementation of authentic assessment. In collecting the data, this research used document study and interview. The data were analyzed through three steps; data reduction, data classification and analysis, and conclusion drawing or data verification. After analyzing the obtained data, the English teachers used five types of authentic assessment namely teacher’s observation, performance, portfolio, project, and peer-assessment. Besides, in the learning instruction, the English teachers did not implement all of the types of authentic assessment in all learning material. Thus, the implementation of authentic assessment needs to be reviewed in order to help the English teachers in implementing the authentic assessment.